2017
DOI: 10.1115/1.4038452
|View full text |Cite
|
Sign up to set email alerts
|

Tool Path Planning for Directional Freezing-Based Three-Dimensional Printing of Nanomaterials

Abstract: As an emerging and effective nanomanufacturing technology, the directional freezing-based three-dimensional (3D) printing can form 3D nanostructures with complex shapes and superior functionalities, and thus has received ever-increasing publicity in the past years. One of the key challenges in this process is the proper heat management, since the heat-induced melting and solidification process significantly affects the functional integrity and structural integrity of the printed structure. A novel approach for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…41,[279][280][281][282] Other than heated solvent evaporation, also freeze drying is applied for 3D printing of silver NWs and graphene aerogels with combined DIW and ink-jet techniques. 164,283,284 But the DIW technique has more advantages, especially in the use of metal nanopowders as inks and paste conductive fillers. Similarly to the use of carbon nanomaterials, a high loading of nanoparticles can be obtained here as well, yet additional thermal sintering of the deposited paste allows obtaining almost solid metallic lines.…”
Section: D Printing With Nanomaterials For Structural Electronicsmentioning
confidence: 99%
“…41,[279][280][281][282] Other than heated solvent evaporation, also freeze drying is applied for 3D printing of silver NWs and graphene aerogels with combined DIW and ink-jet techniques. 164,283,284 But the DIW technique has more advantages, especially in the use of metal nanopowders as inks and paste conductive fillers. Similarly to the use of carbon nanomaterials, a high loading of nanoparticles can be obtained here as well, yet additional thermal sintering of the deposited paste allows obtaining almost solid metallic lines.…”
Section: D Printing With Nanomaterials For Structural Electronicsmentioning
confidence: 99%
“…[ 29 ] Furthermore, they proposed a heuristic tool path planning method. [ 30 ] It was found that the tool path planning highly affects the spatial and temporal temperature distribution of the being printed part, and the optimized tool path planning can effectively improve the uniformity of the temperature distribution. The droplet solidification time in freeze‐nano printing (FNP) governs the thermal distribution and affects both the macro‐structure (e.g., dimension, surface quality) and micro‐structure (e.g., pore size, pore morphology).…”
Section: Ice 3d Printingmentioning
confidence: 99%
“…Among various 3D printing processes, the drop-on-demand inkjet printing has been used to print graphene oxide ink into a truss structure and also print ice to support the bridges above the hollow regions. The building environment has a temperature well below the freezing point [12][13][14][15][16][17][18]. The printed ice will be further removed by the freeze-drying process, leaving an ultra-low-density graphene oxide network.…”
Section: Introductionmentioning
confidence: 99%